PERCEIVED ORGANIZATIONAL SUPPORT: A DETERMINING FACTOR OF AUDITOR PERFORMANCE? - Noor Laeliya, Aida; Chariri, Anis (Jurnal Akuntansi Kontemporer, 2025)
Research Purposes. This study aims to examine the effect of salary, motivation, and organizational culture on auditor performance, with perceived organizational support as a moderating variable. Research Methods. This research uses a quantitative descriptive approach with a survey method. The sample used was 90 auditors who work in Semarang City. Data analysis was performed with multiple linear regression and moderated regression analysis (MRA). Data processing using IBM SPSS version 27 Research Results and Findings. The results showed that salary and motivation had a significant effect on auditor performance, and organizational culture had no effect on auditor performance. Meanwhile, perceived organizational support as a moderating variable shows that it strengthens motivation and organizational culture on auditor performance. However, the perceived organizational support variable cannot moderate the effect of salary on auditor performance. The practical implication of this research is that organizations, especially the Public Accounting Firm (KAP), need to pay more attention to efforts to increase the support felt by auditors.